Analisis Keaktifan Mahasiswa dalam Proses Pembelajaran Statistika Mulitvariat - Irsyad, Taufik; Wuryandini, Endang; Yunus, Mahmud; Hadi, Dwi Prastiyo (Universitas Pendidikan Ganesha, 2020)
This research is motivated by the condition of students in the learning process of multivariate statistics courses. In the matter of data input practice, data output, and data interpretation. Students tend to only follow lectures and are less active in asking questions. Students are less active in looking for additional material beyond the material taught by the lecturer. The research method uses a qualitative case study type approach. The research object consisted of 23 students who took multivariate courses, the Chair of the Study Program and a lecturer in Economic Education. Data collection techniques used were observation, interviews, and documentation. The results of this study are multivariate statistical learning courses performed well. The process of teaching and learning activities prioritize student activity as evidenced by the practice carried out in each lecture. The Submission of material is done using English. Student activeness is still lacking because students are less active in asking questions. Student motivation tends to be low in finding information about lecture material that has been taught or will be taught. The conclusion of this study is that discipline, commitment, and encouragement from within students are important. Personal motivation affects more activeness. This research has implications as a contribution to lecturers in order to be able to increase encouragement from within students in order to increase activity in the learning process.